Viral respiratory infections are contagious, potentially pandemic causing and mostly spread during the winter season. (Homoeopathy for All, 2023)
Cold and flu are contagious respiratory illnesses that are caused by different viruses. A cold is among the most common infection in humans which is caused by more than 100 serotypes of viruses but one common serotype is the rhinovirus. Other serotypes  influenza virus, adenovirus, coronavirus, and the respiratory syncytial virus they are responsible for causing outbreaks and pandemics. The cold caused by rhinovirus is not a serious infection nor life-threatening.
Keywords: viruses; rhinovirus; life-threatening